PERBEDAAN INDEKS KEBUTUHAN PERAWATAN PERIODONTAL (CPITN) ANAK NORMAL DAN ANAK TUNARUNGU - Nashriatul Mawaddah; Kusuma Arbianti; Niluh Ringga W (Odonto : Dental Journal, 2017)
Background: Normal children had sensing capabilities to do oral health assessments. The inability to hear that was suffered by the deaf children caused obstacles to do oral health assessments. The dental and periodontal conditions were important for healthy life in general. The objective of this research was to know the difference Community Index Periodontal Treatment Needs (CPITN) between normal children in SD N 1 Tegaldowo Sragen with deaf children in SLB-B YPSLB Gemolong. Method: This research used observational method with Cross Sectional strategy. The subject of this research consist of 31 deaf children dan 83 normal children. Periodontal conditions from the two groups were measured by WHO probe. After the measurement, the CPITN index would be determined by looking at the highest score. The research was analyzed by using statistic non-parametric test from Mann-Whitney. Results: The result was 0.0003 (p<0.05), revealing there was a significant difference of CPITN index from normal children and deaf children. Conclusion: In conclusion, the highest periodontal status from normal children was gingival bleeding that meant they need to be given a conseling and demonstation about oral helath. The highest score from deaf children revealed the presence of subgingival and supragingival calculus that meant they needed to be given a counseling and demonstration including scaling treatment.